2014
DOI: 10.3109/13813455.2014.950589
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effect and receptor signalling profile of a non-metabolisable insulin glargine analogue

Abstract: ContextInsulin glargine (GLA) is rapidly metabolized in vivo to metabolite M1, which has in vitro metabolic and mitogenic profiles comparable with human insulin (HI).ObjectiveTo investigate the pharmacologic and signalling profiles of a non-metabolizable analogue (A21Gly,DiD-Arg) insulin (D-GLA).MethodsRats were injected s.c. with 1, 12.5 or 200 U/kg of GLA or D-GLA; blood glucose and phosphorylation status of the insulin receptor (IR), Akt and IGF-1 receptor (IGF1R) in tissue samples were investigated after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…As described in the Methods section, a non-metabolisable form of insulin glargine was generated by replacing the L-arginine resides at position 31 and 32 on the B chain of insulin with D-arginine residues (A21Gly,DiD-Arg) [8]. These D-arginines are not cleaved by carboxypeptidases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As described in the Methods section, a non-metabolisable form of insulin glargine was generated by replacing the L-arginine resides at position 31 and 32 on the B chain of insulin with D-arginine residues (A21Gly,DiD-Arg) [8]. These D-arginines are not cleaved by carboxypeptidases.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in vitro studies have found that A21Gly,DiD-Arg has similar affinity for IGF-1R and similar mitogenic potency as insulin glargine in SAOS-2 cells [8]. The A21Gly,DiD-Arg analogue allowed us to model the effects that insulin glargine may have in a tumour-bearing person with the postulated slow rate of metabolism of insulin glargine, and greater exposure to higher circulating levels of the parent glargine than the M1 metabolite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations